Levels of heavy metals in seawater, sediment and in the tissue of Crassostrea belcheri in the western estuary of Ganh Rai bay - Phu, Le Hung; Thu, Nguyen Hong; Ngoc, Pham Hong; Dung, Le Trong; Ha, Dao Viet (Vietnam Journal of Marine Science and Technology, 2021)
Recent studies have shown that the seawater, sediment and commercial bivalve molluscs in the studied area have been contaminated by some heavy metals Zn, Cu, Pb and Cr. Highly toxic heavy metals like As, Cd, Pb, Hg have tended to accumulate in the tissue of clams. This paper presents the levels of some heavy metals in the seawater, sediment and soft part of oyster (Crassostrea belcheri) samples collected from the western estuaries of Ganh Rai bay in 2015 and 2017. The results also showed that Ha Thanh and Rach Lo sites recorded the highest contents of most studied metals in oyster samples. Levels of metals in oyster were in the order of Zn > Cu > As > Pb > Cr > Cd > Hg and the contents of metals in oyster did not reflect a correlation with those in surrounding environment. Concerning food safety criteria, Pb, Cd and Hg contents were lower than acceptable limit given by the compilation of FAO (1983), whereas As, Cu and Zn contents exceeded the legal limit, especially Zn contents. Cu and Cr contents in sediment samples of Nga Bay and Dong Hoa estuaries were between LEL-SEL values (≥ LEL and < SEL), which may cause biological impacts at moderate level.